Body composition and perceived stress levels in transgender individuals after one year of gender affirming hormone therapy - Ceolin, Chiara; Scala, Alberto; Scagnet, Bianca; Citron, Anna; Vilona, Federica; De Rui, Marina; Miscioscia, Marina; Camozzi, Valentina; Ferlin, Alberto; Sergi, Giuseppe; Garolla, Andrea; , the GIIG group (Frontiers in Endocrinology, 2024)
Background: Higher stress levels are linked to increased body fat and decreased bone density, effects that can be exacerbated by lifestyle choices. This is particularly relevant for transgender and gender diverse (TGD) individuals, who often face additional stress from transphobia and social stigma. However, there is limited research on how stress affects body composition and bone health in TGD individuals, particularly in relation to gender-affirming hormone therapy (GAHT). This study examines the impact of perceived stress on these factors in TGD individuals before and after one year of GAHT, compared to a cisgender control group.: The study assessed 181 individuals, including 74 TGD participants (44 assigned female at birth [AFAB] and 30 assigned male at birth [AMAB]) and 107 controls (56 AFAB and 51 AMAB). Fifty-seven TGD participants completed follow-up one year after starting GAHT. Data collected included clinical history, blood tests, body composition, bone density, and quality of life assessments (Patient Health Questionnaire-9 [PHQ-9] and Perceived Stress Scale [PSS]).Results: After one year of GAHT, TGD AFAB individuals showed a bone mineral density (BMD) similar to cisgender AMAB individuals, while TGD AMAB individuals' BMD remained significantly lower than cisgender controls. TGD AFAB individuals experienced increases in muscle strength (+8% from baseline), while TGD AMAB individuals showed a 24% increase in fat mass from baseline and an approximate 8% reduction in lean mass. PSS and PHQ scores, initially higher in TGD individuals, did not change significantly after one year of GAHT. A significant correlation was found between body fat percentage and PHQ and PSS scores at baseline and one year after GAHT, respectively.Conclusions: These findings reveal a complex relationship between GAHT, body composition, and perceived stress in TGD individuals, highlighting the need for further research on stress and health outcomes in this population.